If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5y + 5 = -9y Reorder the terms: 5 + -5y = -9y Solving 5 + -5y = -9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '9y' to each side of the equation. 5 + -5y + 9y = -9y + 9y Combine like terms: -5y + 9y = 4y 5 + 4y = -9y + 9y Combine like terms: -9y + 9y = 0 5 + 4y = 0 Add '-5' to each side of the equation. 5 + -5 + 4y = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 4y = 0 + -5 4y = 0 + -5 Combine like terms: 0 + -5 = -5 4y = -5 Divide each side by '4'. y = -1.25 Simplifying y = -1.25
| -17w-2=15w | | 0.7*2.4+16+4*2.4=27.28 | | x+3=2/9 | | 11/20= | | 2m+9m=33 | | 3.33=-3(9+n) | | 8x+1=7x-20 | | 50/100= | | 5x+3(10)=3.5(x+10) | | 20/1000= | | 4.3333(4.6666p-.25)=91.3611 | | 4y+18y=66 | | 8-4n=6n+2 | | -3y+9=-4y+3 | | 20/100= | | -10=-7+h | | -2x^3-2x^2=-40x | | 6x-6=9x-36 | | 20.2217(4.6666p-.25)=91.3611 | | 6x-6=9x-20 | | 6/10= | | .60= | | 20=-5x+2y | | 8-4n=6n | | 11x+16=2x+7 | | 37/50= | | 6z+24=6(z+4) | | 96=-4(6x-6) | | -3(3b+3)+(10b-2)=0 | | 4(3x+2)=2(6x+4) | | 45=x+34 | | p=32.50-4d+3.50 |